Legal Problems of Land Services Online - Farid Wajdi; Rahmat Ramadhani (International Journal Reglement & Society (IJRS), 2022)
The problem of online land services by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) has several legal problems related to the nature of land registration to ensure legal certainty as its main substance. The problem to be discussed is regarding the online land service policy implemented by the National Land Agency with various obstacles and legal problems that arise against the policy. The research method used is normative legal research. The results showed that in terms of online land services, for the first time registration activities, especially in physical land measurement services, it could not be carried out online so that the substance of online land service policies could not be fully implemented. The lack of public knowledge about technology makes it difficult to access land services online, which becomes a separate obstacle in implementing online land service policies